2017
DOI: 10.1186/s12940-017-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of current and future concentrations of air pollutants on respiratory disease risk in England

Abstract: BackgroundEstimating the long-term health impact of air pollution in a spatio-temporal ecological study requires representative concentrations of air pollutants to be constructed for each geographical unit and time period. Averaging concentrations in space and time is commonly carried out, but little is known about how robust the estimated health effects are to different aggregation functions. A second under researched question is what impact air pollution is likely to have in the future.MethodsWe conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…The ability to model air quality at the regional scale will be particularly important for health impact modelling where high spatial resolution is important to allow the concentration variations to be matched to population locations. Indeed, the techniques in this paper have already been applied to 2050s climate and air quality in Pannullo et al (2017) Tables A2, A3, and A4. Lock et al (2000) and Lock (2001) with scalar flux-gradient option Lock et al (2000) and Lock (2001) (Smith, 1990) Microphysics (large-scale precip) Wilson and Ballard (1999) enhanced for PC2 and graupel Wilson and Ballard (1999) Radiation Edwards and Slingo (1996) with Cusack et al (1999) for gaseous absorption and incremental adjustments to fluxes and cloud between full radiation time steps (time stepping The method for deriving AQUM emissions of VOCs from RCCM emissions is described in Sect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to model air quality at the regional scale will be particularly important for health impact modelling where high spatial resolution is important to allow the concentration variations to be matched to population locations. Indeed, the techniques in this paper have already been applied to 2050s climate and air quality in Pannullo et al (2017) Tables A2, A3, and A4. Lock et al (2000) and Lock (2001) with scalar flux-gradient option Lock et al (2000) and Lock (2001) (Smith, 1990) Microphysics (large-scale precip) Wilson and Ballard (1999) enhanced for PC2 and graupel Wilson and Ballard (1999) Radiation Edwards and Slingo (1996) with Cusack et al (1999) for gaseous absorption and incremental adjustments to fluxes and cloud between full radiation time steps (time stepping The method for deriving AQUM emissions of VOCs from RCCM emissions is described in Sect.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 2 a comparison of the percentage of observations/model values greater than the 65.0 µg m −3 threshold is also included; it illustrates that AQUM-h simulates observed frequencies of higher NO 2 concentrations well, making it better suited to calculating health burdens due to elevated levels of NO 2 (e.g. Pannullo et al, 2017). However, shown in Fig.…”
Section: Comparison Against In Situ Observationsmentioning
confidence: 99%
“…For example, Dominici et al () used PM 2.5 data in the Air Quality System database and found their associations with cardiovascular and respiratory hospital admissions. Pannullo et al () used PM 2.5 data on a 12 km × 12 km regular grid in England and studied the impact of PM 2.5 on respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Dust storms transport yearly ⁓2.2 billion tons of soil and dry sediments throughout the earth [2] . Furthermore, many studies reported increased hospital admittance for respiratory and cardiovascular diseases owing to exposure to dust storms [3,4] . In addition to the public health effects, the agriculture, air traffic, and tourism are also affected [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Dust storms are one of the major natural sources of respirable particulates in Kuwait State [10,11] . Several European [3,12] , USA [13] , Middle East [7,14] , Kuwait [15,16] , and Chinese studies [17] revealed high risk of lung cancer, heart diseases, and chronic obstructive lung diseases among those exposed to PM10.…”
Section: Introductionmentioning
confidence: 99%